An exceptionally thick Middle Pleistocene tephra layer from Epirus, Greece - Pyle, D; van Andel, T; Paschos, P; van den Bogaard, P (1998)
A newly recognized 2-m-thick trachytic volcanic ash deposit from northwestern Greece is dated at 374 000 ± 7000 yr and correlated with the Middle Pleistocene volcanic activity of central Italy. The deposit represents ash fallout from one of the largest volcanic eruptions in Europe of the past 400 000 yr and should provide an important stratigraphic marker within the poorly dated Middle Pleistocene deposits of Italy and Greece.